The importance of historical and cultural Islamic studies and factors contributing to its prosberity - Karhili , Nabeel (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Research of historical and cultural studies aimd at the development that has developed since ancient times until today. And its impact on the Unted Nations and these studies are preliminary to the advancement of the Islamic world. And to identify the origin of the way of origin and composition. To reach this end it was necessary to identifg the factors of its prosperity from the stability of the situation of the country and the attention of referees and scientific missions …etc. Hence, it was necessary to adress the classification of these works because classification it self is advelopment. And the books of the two countries. Books of history , books of translations. Books of encyclopedias and countries in addition to geograghical studies and in the filed of medicine, pharmacy, chemistry, astronomy…etc. And then address the benefits of these studies , which contribute to the advancement of civilization. These studies how ever varied are special facility for intellectual life. Anumber of researchers were drawn out. This study come out with asset of educational, religious and cultural.